Analysis of Potential Economic Value of Catfish Cultivation Waste as LOF in Benteng Somba Opu Village, Gowa Regency - Benny Audy Jaya Gosari; Aris Baso; Amilluddin Amilluddin; Sri Suro Adhawati; Abdul Wahid; Salman Salman (Jurnal Social Economic of Agriculture, 2022)
The catfish wastewater is directly discharged into the environment, it will disrupt the lives of both humans and other organisms. This study aims to determine the amount of macronutrients nitrogen, phosphate, and potassium from catfish farming waste as liquid organic fertilizer (LOF) through the fermentation process at different times, and to determine the potential economic value, by determining the cost of production and selling price of waste products. Cultivation of catfish as LOF in Benteng Somba Opu Village, Barombong District, Gowa Regency. This research was carried out from February to April 2021. The potential economic value used a quantitative descriptive research method. The results of the study on catfish culture wastewater containing LOF also provide additional income for catfish cultivators. HPP based on research results is Rp. 19,000 /L. After calculating the cost of production, the potential profit for LOF from catfish farming waste in 1 liter is Rp. 3,400 /L, with a waste potential of 6,000 L / month, the economic potential value is Rp. 20.400.000,- with pool type permanent pool (L=3m, W =2 m, H=1,5m) and can still increase depending on the amount of catfish production in a month. RCR value of 1,24  that the LOF business is efficient and profitable to continue to operate. Although the potential is small, it is quite interesting for catfish cultivators to try.